KOnsep State Amien Rais dan Nurcholis Madjid - Andri Nirwana AN (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
This paper focuses on the study of Islamic Political Thought of Nurcholish Madjid and M. Amien Rais about Islamic state in Indonesia. Nurcholish Madjid required secularization, as an effort and rationalization of religious desecration. In this context, religion is not only understood as an integral dimension of the sacred (holy) with all its appliances. But there are many parts changed, because it is sociological. According to Nurcholish, secularization is the way that Muslims needed to be done, so that the public can distinguish between social phenomena and the phenomenon of transcendent revelation.